Dynamic modelling of a vapour compression air conditioner system (2009)
Modelling is a very important tool for understanding complex problems. A model plays a fundamental role in the analysis, design and development of complex systems, especially when physical testing and experimentation are not feasible - or not possible at all. Modelling technology holds tremendous promise for reducing costs, improving quality, and shortening the time-to-market for manufactured goods. Unfortunately, this technology still remains largely underutilized by industries today, especially in Nigeria. Analyzing vapour compression air conditioners for their capability of achieving a desired performance level is a difficult and essential task that must be undertaken by the specifying engineer. This involves an understanding of what is required for the particular air conditioning application as well as what the particular grouping of equipment components into the system are or, more importantly, are not capable of doing. A detailed dynamic model of a vapour compression air conditioner system is therefore developed. The Model components are mathematically described, considering energy balances within the system. Ambient wet and dry bulb temperature and solar radiation are the few required inputs. Output measures of performance of the system such as system temperatures, energy flows, and coefficient of performance can be predicted. Simultaneously, a software package, "AJBSIM' has been developed to simulate the steady state performance of the equipment, ease and hasten the calculation expedience involved as well as enable parametric studies to be conducted.